Hematological characteristics, oxidative stress, and patient-reported symptoms in Tibetan patients with chronic mountain sickness at 4500 m altitude - Zhong, Yang; Zhang, Fengying; Li, Qiuyue; Hao, Doudou; Shi, Zhiyou; Liu, Yuling; Zhu, Suying; Tsering, Pasang; Wu, Yunhong (Frontiers in Physiology, 2025)
BackgroundChronic mountain sickness (CMS), driven by chronic hypoxia, features erythrocytosis, cardiovascular impairment, and systemic oxidative stress. Current studies focus on haematological and cardiopulmonary changes, but multidimensional features like sleep disturbances, quality of life, and oxidative stress remain underexplored.MethodsThe cross-sectional study included 47 adult Tibetan residents living at 4,500 m and diagnosed with CMS using Qinghai criteria. Blood samples were collected, and questionnaires assessed quality of life, fatigue, and sleep. Multivariate logistic regression was used to explore associations between variables, using CMS comorbid with high-altitude polycythemia (HAPC) or sleep disturbance as endpoints.ResultsThe mean age of patients was 40.57 ± 6.21 years (29 males, 18 females). Males had higher RBC, HGB, HCT, UA, and T-AOC levels (all P < 0.001). A moderate to strong positive correlation was observed between these markers. 91.67% of patients with comorbid HAPC were males with severe CMS. Lower MCHC (OR = 0.80, P = 0.02) and higher T-AOC (OR = 1.47, P = 0.02) were associated with HAPC. Males (OR = 0.11, P = 0.03), higher 8-OHdG levels (OR = 0.95, P = 0.03), higher body pain scores (OR = 0.91, P < 0.01), and higher general health scores (OR = 0.90, P = 0.02) were more likely to report good sleep quality.ConclusionMales with CMS had higher T-AOC and better sleep quality than females. Good sleep quality was associated with better quality of life and less fatigue. Oxidative stress indicators correlated with clinical phenotypes, but causality requires further investigation. This trial was registered at Chinese Clinical Trial Registry (ChiCTR2400082685).